Main Aspects of the Reception and Conveyance of Irony in the Earliest English Versions of Celestina - Mª Ángeles Ruiz Moneva (Celestinesca, 2021)
Celestina (Rojas, 1499/ ca.1502) was shortly after translated into English in the Elizabethan period, in very different literary forms, which would be best approached as «re-creations», rather than translations proper (Murillo 1994, 1992): Rastell’s version (1525), written in the form of an interlude, and Captain Stevens' The Bawd of Madrid (1707), as a narrative piece. Only Mabbe’s Celestine (1631) is formally similar to Rojas's work. Irony has always been acknowledged by critics as an essential element of the message conveyed by Rojas. On the whole, the genre shifts that Rastell's and Stevens' works underwent may be expected to influence the way irony is conveyed. On the other hand, although Mabbe's version follows the main structure and themes of the original, some essential features of this version lie at the core of some peculiar interpretations of irony.